2010
DOI: 10.1371/journal.pone.0010178
|View full text |Cite
|
Sign up to set email alerts
|

T- and B-Cell-Mediated Protection Induced by Novel, Live Attenuated Pertussis Vaccine in Mice. Cross Protection against Parapertussis

Abstract: BackgroundDespite the extensive use of efficacious vaccines, pertussis still ranks among the major causes of childhood mortality worldwide. Two types of pertussis vaccines are currently available, whole-cell, and the more recent acellular vaccines. Because of reduced reactogenicity and comparable efficacy acellular vaccines progressively replace whole-cell vaccines. However, both types require repeated administrations for optimal efficacy. We have recently developed a live attenuated vaccine candidate, named B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Although early studies indicated that CD8 + T cells are not necessary for protection against pertussis (39,40), recent data IgA memory B cells may be a consequence of the slow onset of PT expression during the colonization process in the nasal cavity, unlike FHA, PRN, and FIM, which are fully expressed during initial stages of colonization (43). In any event, these data suggest that B. pertussis antigens other than PT in BPZE1 do elicit an IgA response.…”
Section: Resultsmentioning
confidence: 84%
“…Although early studies indicated that CD8 + T cells are not necessary for protection against pertussis (39,40), recent data IgA memory B cells may be a consequence of the slow onset of PT expression during the colonization process in the nasal cavity, unlike FHA, PRN, and FIM, which are fully expressed during initial stages of colonization (43). In any event, these data suggest that B. pertussis antigens other than PT in BPZE1 do elicit an IgA response.…”
Section: Resultsmentioning
confidence: 84%
“…A single nasal BPZE1 vaccination led to strong protection against colonization by B. parapertussis (9) and protection could be transferred by splenocytes but not by serum of BPZE1-vaccinated mice, whereas serum from convalescent mice was able to protect against re-challenge with B. parapertussis . These observations indicate that BPZE1-mediated cross-protection was cell-mediated (12). Bordetella bronchiseptica can infect a large variety of mammalian species, including humans, and can cause mild to severe cough.…”
Section: Heterologous Protection By Bpze1mentioning
confidence: 83%
“…In addition to B. pertussis , BPZE1 protects mice also against lung infection by other Bordetella species, although this was not observed after vaccination with aPV (9, 12, 19). Bordetella parapertussis is a respiratory pathogen that causes chronic pneumonia in sheep or pertussis-like disease in humans, albeit usually less serious than pertussis caused by B. pertussis .…”
Section: Heterologous Protection By Bpze1mentioning
confidence: 97%
“…More recently, the ability of B. pertussis to skew the host immune response towards the expansion of Th17 cells was observed. In mice, pertussis infection or immunization with the whole cell vaccine induce a Th17 response and the generation of antigen-specific Th17 cells correlates with protection [ 32 , 33 , 34 , 35 ]. In agreement with these results, it has been shown that human monocyte-derived DC infected ex vivo with B. pertussis induce a mixed Th1/Th17 polarization of CD4 + T cells [ 36 , 37 ].…”
Section: Immunity To B Pertussismentioning
confidence: 99%